PERUBAHAN STATUS SOSIAL EKONOMI MASYRAKAT DI DUSUN SEPAKAT DESA GANTING DAMAI KECAMATAN SALO KABUPATEN KAMPAR - Elvira, Maya; Yusuf, Yusmar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study analyzed the changes in socio-economic status in the dusun Sepakat. This phenomenon is a social phenomenon that occurs in people who have low socio economic status change for the better. The theory used is the theory of social change. Data analysis was conducted to address the existing problems in this research is qualitative descriptive approach further analyzed based on the theories in the study and presented in narrative form qualitatively, informants in this study were 8 people consisting of seven heads of families, a man who once served as the village chief. From the results of research in the field that the development of infrastructure such as paved roads and footpaths were carried out to bring change to the socio economic status of people in dusun Sepakat. The construction carried out in the dusun Sepakat going well despite the circumstances dusun located in the middle of the Kampar river and flanked by two bridges Hanging. Social change in the community there are five aspects such as housing, employment, income, area of plantation land ownership and education. Changes in socio-economic status can be seen from the changes in community development efforts such as rubber and oil palm plantation ownership, ownership of shops and small stalls and animal husbandry. The main occupation of people in dusun Sepakat once only as a vegetable farmers, but now turned into rubber and oil palm growers. Land community garden not only in the dusun but there are also outside the dusun.Keywords: Development, Social Change, Socio-Economic Status